Executive/Board medical background and corporate resilience during the COVID-19 pandemic - Huang, J.; Cao, June; Zhao, J. (Elsevier, 2023)
The study investigates the impact of the CEO/board medical background on stock return reactions to COVID-19. CEOs/boards having a medical background possess a knowledge advantage, which enables them to identify risks earlier, take faster action and better prepare for business operations in response to pandemic shocks. Using data from China between January 1st and March 31st, 2020, we find that firms with CEOs or board members having medical background experienced a less severe pandemic-related decline in stock returns. This effect is more evident for firms having a powerful CEO, with more medical directors and located in cities with fewer medical resources. Better operating performance and more investment activities are underlying mechanisms that result in the outperformance of firms with medical expertise. Overall, our findings highlight the critical role of the expertise and experiences of senior executives in shaping the responses to adverse events.